Algorithms for journalism: The future of news work - Lindén, Carl-Gustav (The Journal of Media Innovations, 2017)
Software-generated news, sometimes called “robot journalism,” has recently given rise to concerns that the automation of news will make journalists redundant. These arguments follow a deterministic line of thinking. Algorithms choose information for users but are also the construct of social process and practice. The aim of this essay is to explore “the algorithmic turn” (Napoli, 2014) in news production. Based on case studies from three separate news outlets it is found that the impact of automated news is, first, increased efficiency and job satisfaction with automation of monotonous and error-prone routine tasks; second, automation of journalism routine tasks resulting in losses of journalist jobs; and third, new forms of work that require computational thinking.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNTYxNy9qbWkudjRpMS4yNDIw